Rancang Bangun Sistem Kontrol Ph Air dan Pemberian Pakan Ikan Otomatis Pada Akuaponik Berbasis Mikrokontroler - Pradana, Ersa Satria; Ch, Syafaruddin; Suksmadana, I Made Budi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Aquaponics is an integrated system that combines fish farming and plant cultivation in a mutually beneficial ecosystem. In this system, plants utilize nutrients produced from fish waste, while also helping to maintain water quality. However, farmers often face difficulties in managing water pH and feeding fish due to their busy schedules or other activities. And also excess feeding can accelerate changes in pond pH. This is because the remaining uneaten feed will decompose in the water, resulting in ammonia compounds that have the potential to increase the pH in the pond. Therefore, this research aims to design an automated device to regulate feeding and control water pH. Arduino is used as the central controller to manage sensors and automate the system. Water quality is measured using a pH sensor with an accuracy level of 95%. The pH control system in fish ponds functions to maintain water quality at the optimal range for fish health. Feeding is carried out according to a set schedule, and the feed throwing distance is adjusted based on voltage. The results of this system show that water pH remains stable, fish and plants are in good condition, and it helps farmers easily maintain water quality and nutrients for both fish and plants. Thus, this device can provide a practical solution for farmers needing automation in the aquaponics process.